The Critical Success Factors Of Mobile Entrepreneur Programme By Lembaga Zakat Selangor - Md Hassan, Nurbani (2021)
There are three (3) objectives in this study, such as evaluating the implementation process of MEP, examining the critical factors (CSFs) contributing to the Asnaf entrepreneurs’ success, and investigating the issues or challenges experienced by LZS and Asnaf entrepreneurs in this programme